Super-resolution microscopy in studying neuroendocrine cell function - Bost, Anneka; Pasche, Mathias; Schirra, Claudia; Becherer, Ute (Frontiers in Neuroscience, 2013)
The last two decades have seen a tremendous development in high resolution microscopy techniques giving rise to acronyms such as TIRFM, SIM, PALM, STORM, and STED. The goal of all these techniques is to overcome the physical resolution barrier of light microscopy in order to resolve precise protein localization and possibly their interaction in cells. Neuroendocrine cell function is to secrete hormones and peptides on demand. This fine-tuned multi-step process is mediated by a large array of proteins. Here, we review the new microscopy techniques used to obtain high resolution and how they have been applied to increase our knowledge of the molecular mechanisms involved in neuroendocrine cell secretion. Further the limitations of these methods are discussed and insights in possible new applications are provided.